2015
DOI: 10.1177/1071100715604392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Total Ankle Arthroplasty Outcomes

Abstract: Level III, retrospective comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…15,23 A retrospective study found an increased long-term risk of implant failure in obese patients (BMI 30-45 kg/m 2 ), especially with the diagnosis of primary osteoarthritis. 31 While several studies have shown comparable success and complications between obese and nonobese patients, further studies are required to demonstrate outcomes specific to morbidly obese patients (BMI >40 kg/m 2 ). 1,2,6 Poorly controlled diabetes with neuropathy posed substantial challenge in wound healing, potential infection, postoperative weightbearing, and the development of Charcot's arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…15,23 A retrospective study found an increased long-term risk of implant failure in obese patients (BMI 30-45 kg/m 2 ), especially with the diagnosis of primary osteoarthritis. 31 While several studies have shown comparable success and complications between obese and nonobese patients, further studies are required to demonstrate outcomes specific to morbidly obese patients (BMI >40 kg/m 2 ). 1,2,6 Poorly controlled diabetes with neuropathy posed substantial challenge in wound healing, potential infection, postoperative weightbearing, and the development of Charcot's arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…9 TAA in patients with a BMI > 30 have been recently shown to have a higher probability of implant failure at 5 years. 19 In addition, it has been demonstrated that BMI > 30 leads to a higher 90 day perioperative complication rate after TAA with 4.7% infection rate and 4.7% local complication rate. 23 Our infection rate in these patients was 7.1%.…”
Section: Discussionmentioning
confidence: 99%
“…This is less than the reported 20.6% rate found in the literature, however our study size was underpowered and we had a significantly shorter follow-up. 19 In addition to obesity, the patient who developed a wound infection had rheumatoid arthritis and was taking prednisone and Orencia (Abatacept). Complications after foot and ankle surgery in patients with rheumatoid arthritis is a well-known issue due to the nature of this systemic disease and the medications used to treat it.…”
Section: Discussionmentioning
confidence: 99%
“…Although many investigations have evaluated the association of BMI and surgical complications in their secondary analyses (51,(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84), we identified 20 studies with hypotheses specifically addressing the effect of obesity on lower extremity surgery (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). These included studies on total ankle arthroplasty, pilon fracture ORIF, ankle fracture ORIF, calcaneal fracture ORIF, ankle arthrodesis, Achilles tendon repair, ankle arthroscopy, flatfoot reconstruction, and elective forefoot reconstruction.…”
Section: Preoperative Considerationsmentioning
confidence: 99%